Characterising the evidence base for advanced clinical practice in the UK: a scoping review protocol. Issue 5 (20th May 2020) - Evans, Catrin; Poku, Brenda; Pearce, Ruth; Eldridge, Jeanette; Hendrick, Paul; Knaggs, Roger; McLuskey, John; Tomczak, Philippa; Thow, Ruaridh; Harris, Peter; Conway, Joy; Collier, Richard
Abstract : Introduction: A global health workforce crisis, coupled with ageing populations, wars and the rise of non-communicable diseases is prompting all countries to consider the optimal skill mix within their health workforce. The development of advanced clinical practice (ACP) roles for existing non-medical cadres is one potential strategy that is being pursued. In the UK, National Health Service (NHS) workforce transformation programmes are actively promoting the development of ACP roles across a wide range of non-medical professions. These efforts are currently hampered by a high level of variation in ACP role development, deployment, nomenclature, definition, governance and educational preparation across the professions and across different settings. This scoping review aims to support a more consistent approach to workforce development in the UK, by identifying and mapping the current evidence base underpinning multiprofessional advanced level practice in the UK from a workforce, clinical, service and patient perspective. Methods and analysis: This scoping review is registered with the Open Science Framework (https://osf.io/tzpe5 ). The review will follow Joanna Briggs Institute guidance and involves a multidisciplinary and multiprofessional team, including a public representative. A wide range of electronic databases and grey literature sources will be searched from 2005 to the present. The review will include primary data from any relevant research, audit or evaluation studies. All review steps will involve two or more reviewers. Data extraction, charting and summary will be guided by a template derived from an established framework used internationally to evaluate ACP (the Participatory Evidence-Informed Patient-Centred Process-Plus framework). Dissemination: The review will produce important new information on existing activity, outcomes, implementation challenges and key areas for future research around ACP in the UK, which, in the context of global workforce transformations, will be of international, as well as local, significance. The findings will be disseminated through professional and NHS bodies, employer organisations, conferences and research papers.